Penggunaan Metode CTL dengan Media Gambar Seri untuk Meningkatkan Kemampuan Menulis Kelas III SDN Teguhan 3 Kecamatan Paron, Kabupaten Ngawi Tahun Pelajaran 2021/2022 - Anik Puji Rahayuningsih; Muhammad Hanif; Dwi Rohman Soleh (Wewarah: Jurnal Pendidikan Multidisipliner, 2023)
This study describes the use of the CTL method with picture series media to improve Writing Skills for third grade indonesian language subjects at SDN Teguhan 3, Paron District, Ngawi Regency Academic Year 2021/2022. This study uses a qualitative approach with the type of classroom action research spiral model from Kemmis and Taggart. The steps in the spiral model according to Kemmis and Taggart consist of action planning, action implementation, observation and reflection. This action research was conducted in two cycles. Data were collected through tests, observations, interviews and documentation. The data analysis technique in this research is qualitative data analysis. The data obtained in each cycle in the form of student activity data and data on the ability to write simple essays in learning to write essays using the CTL method and pictures series media. Results of the study, it was found that the use of the CTL method with pictures series media increased the activeness and motivation of writing essays. In the first cycle, the students' activities 71.72 increased by 13.13% to 84.85% in the second cycle. The use of the CTL method with pictures series media increases the ability to write essays. The average value in the pre-cycle was 61.11, in the first cycle increased to 70.00, while in the second cycle it reached 81.67. For class classical completeness in the pre-cycle 33.33%, increased in the first cycle to 66.67%, and 88.89% at the end of the second cycle. We can conclude that the use of the CTL method with pictures series media can increase activity and motivation as well as the ability to write essays for third grade SDN Teguhan 3 Paron District academic year 2021/2022.